Assessment of plantation-grown Eucalyptus pellita in Borneo, Malaysia for solid wood utilisation. Issue 1 (2nd January 2017) - Hii, S.Y.; Ha, K.S.; Ngui, M.L.; Ak Penguang, S.; Duju, A.; Teng, X.Y.; Meder, R.
ABSTRACT: Eucalyptus pellita has traditionally been grown in South-East Asia as a fibre source, particularly for pulp production. It has also been identified as a potential species to complement native hardwoods for solid wood and veneer production. However very little information is available in the literature on the mechanical and processing properties of E. pellita, particularly for plantation-grown trees in the tropics. Individual trees from two sites (7-year-old and 9-year-old) in the Malaysian state of Sarawak were selected for recovery trials of solid wood and veneer. The major impediment to utilisation of both solid wood and veneer is the high incidence of end-splitting, particularly for solid wood where the mean green board to air-dry board recovery was only 31%. In addition, the presence of knots in the veneer was undesirable but neither site was maintained for veneer production or had been pruned. The mechanical properties (strength, stiffness, hardness and density) were all sufficient to suggest E. pellita, when properly managed is ideal for solid wood production (flooring, furniture) and appearance-grade veneer.